Signaling in Auctions: Experimental Evidence - Olivier Bos; Francisco Gomez-Martinez; Sander Onderstal; Tom Truyts (Tinbergen Institute, 2017)
We study the relative performance of the first-price sealed-bid auction and the second-price sealed-bid auction in a laboratory experiment where bidders can signal information through their bidding behavior to an outside observer. We consider two different information settings: the auctioneer reveals either the identity of the winning bidder only, or she also reveals the winner's payment to an outside observer. We find that the first-price sealed-bid auction in which the winner's payment is revealed outperforms the other mechanisms in terms of revenue and efficiency. Our findings may have implications for the design of charity auctions, art auctions, and spectrum auctions.
Keywords: C92; D44; D82; 330; Auctions; Signaling; Experiments